2008
DOI: 10.1350/jcla.2008.72.5.525
|View full text |Cite
|
Sign up to set email alerts
|

Proposals for Reforming the Law of Self-Defence

Abstract: The English law of self-defence has attracted significant attention following the controversial decision of the Court of Appeal in R v Martin. At the heart of the controversy is the determination of the reasonableness of a defendant's apprehension of the necessity to use a particular amount of force in self-defence. When comparing the defendant's apprehension and actions to those of a reasonable person in the same circumstances, what characteristics of the defendant must be attributable to the reasonable perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…43 The objectivity of the hypothetical reasonable person involves conceptualising a person that possesses universal characteristics, rather than characteristics personal and peculiar to the defendant. 44 It is assumed that people are mentally sound, rational and prudent. In R v Martin 45 the Court of Appeal suggested that, in exceptional circumstances which made the evidence especially probative, a court could take into account the fact that the defendant was suffering from a psychiatric condition.…”
Section: Reasonable Forcementioning
confidence: 99%
“…43 The objectivity of the hypothetical reasonable person involves conceptualising a person that possesses universal characteristics, rather than characteristics personal and peculiar to the defendant. 44 It is assumed that people are mentally sound, rational and prudent. In R v Martin 45 the Court of Appeal suggested that, in exceptional circumstances which made the evidence especially probative, a court could take into account the fact that the defendant was suffering from a psychiatric condition.…”
Section: Reasonable Forcementioning
confidence: 99%